1994
DOI: 10.1002/food.19940380210
|View full text |Cite
|
Sign up to set email alerts
|

Rapeseed meal‐glucosinolates and their antinutritional effects Part 4. Goitrogenicity and internal organs abnormalities in animals

Abstract: This paper surveys the literature concerning biological properties of rapeseed glucosinolates, chiefly the goitrogenic activity of these compounds and their influence on the morphological and histological abnormalities of internal organs in animals. An attempt has been made to establish threshold glucosinolate levels in diet which trigger the onset or increase of internal organs impairment in animals depending on their species and breeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 72 publications
(35 reference statements)
4
53
1
Order By: Relevance
“…Increased discharge of prolactin provokes thyrotropin-releasing hormone (TRH) within the system of the negative feedback control into hypothyroidism (Aron et al, 1997). Pathohistological findings in chicks involved in our experiment agree fully with the findings of Rotkiewicz et al (1990), Chrappa et al (1991), Mawson et al (1994) and Khan et al (1996), who fed their chicks with diets containing 10%, 15% and more, respectively, thus achieving a significant goitrogenic effect of glucosinolates contained in rapeseed meal. The results differ from those obtained by Kloss et al (1994), who observed no pathohistological changes in internal organs of chicks fed on 10% of crambe (Crambe abyssinica) meal per ration.…”
Section: Discussionsupporting
confidence: 81%
“…Increased discharge of prolactin provokes thyrotropin-releasing hormone (TRH) within the system of the negative feedback control into hypothyroidism (Aron et al, 1997). Pathohistological findings in chicks involved in our experiment agree fully with the findings of Rotkiewicz et al (1990), Chrappa et al (1991), Mawson et al (1994) and Khan et al (1996), who fed their chicks with diets containing 10%, 15% and more, respectively, thus achieving a significant goitrogenic effect of glucosinolates contained in rapeseed meal. The results differ from those obtained by Kloss et al (1994), who observed no pathohistological changes in internal organs of chicks fed on 10% of crambe (Crambe abyssinica) meal per ration.…”
Section: Discussionsupporting
confidence: 81%
“…However, rapeseed is characterized by a high content of glucosinolates. Glucosinolate intake has been found to decrease the utilization of iodine in the thyroid gland, resulting in low levels of triiodothyronine and thyroxine [17, 18]. In our previous experiments, Tvrdá et al [19] found that the substitution of soybean (Glycine max) meal with 00-quality DRS (representing 14% of the total diet) in rat diets did not result in any harmful effects on the biochemical or hematological response of the rats.…”
Section: Introductionmentioning
confidence: 89%
“…The glucosinolates and their hydrolysis products can negatively affect the thyroidal functions and the feed acceptance because of their bitter taste, from there the feed intake and correspondingly the fish growth performance (Bell, 1993;Mawson et al, 1994;Burel et al, 2000;Burel et al, 2001). The phenolic acid such as sinapic acid causes also a bitter taste.…”
Section: Process Designmentioning
confidence: 99%